Evaluation of semi-distributed hydrological models performance in borkena watershed; upper awash basin, Ethiopia - Geteneh Teklie Alemu; Mamaru Moges Ayalew; Berhanu Sinshaw Geremew; Bayu Geta Bihonegn; Kassa Abera Tareke (Heliyon, 2023)
Flood is one of the most significant disasters in human life and economic destruction. To challenge this disaster, the use of models is very important to predict the magnitude and impact of river flow and to find a solution of the problems. This research is aimed to compare the performance of semi-distributed hydrological models in the Borkena watershed. The selected semi-distributed hydrological models were soil and water assessment tool (SWAT), hydrological engineering center-hydrologic modeling system (HEC-HMS), hydrologiska byråns vattenbalansavdelnin (HBV), and parameter efficient distribution (PED). The models were calibrated from 1999 to 2009 and validated from 2010 to 2015 using daily data. Based on validation results; The Nashsutclif (NSC) output of the SWAT, HEC-HMS, HBV, and PED models were 0.68. 0.66, 0.65, and 0.65, coefficient of determination (R2) 0.69, 0.67, 0.71, and 0.70, percentage of bias (PBIAS) −6.5, 0.6, 27.34, and 10.28, and root mean square error (RMSE) 14.24, 17.45, 17.63 and 0.91, respectively. Based on the models' performance results in Borkena watershed, the first effective model was SWAT and the second one was HEC-HMS. The HBV and PED models took third and fourth places respectively. The overall results show that the two infiltration excess models (SWAT and HEC-HMS) were performed in a better way than the two saturation excess models (HBV and PED) on this watershed. Therefore, according to the model output, the Borkena watershed is an infiltration excess area.